Low-modulus high-elongation antifouling weather-resistant sealant as well as preparation method and application thereof

By layering and stripping and modifying talc powder, combined with silane oligomers, anti-fouling weather-resistant sealant with low modulus and high elongation, the problems of sealant pollution and corrosion in ancient building restoration were solved, and the problem of sealant pollution and corrosion in ancient building restoration was achieved. Low modulus, high elongation and anti-fouling effects.

CN119307224AActive Publication Date: 2025-01-14GUANGZHOU BAIYUN CHEM IND +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411665327.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing sealants with low modulus and high elongation have pollution and corrosion problems in the restoration of ancient buildings, and their bonding strength will damage the building substrate and it is difficult to meet the high displacement level requirements of ancient buildings.

Method used

By layering and stripping and modifying the talc powder, combined with silane oligomers as crosslinking agents, an anti-fouling weather-resistant sealant with low modulus and high elongation is prepared to avoid the use of plasticizers and small molecules crossing Coupling agent, dehydration sealant is used to reduce internal stress and contamination.

Benefits of technology

It has achieved the reduction of the modulus strength of the sealant and increased elongation, reduced stress on fragile structures, avoided pollution and corrosion, and is suitable for ancient building restoration and other low-modulus anti-fouling building sealing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144448040000091
    Figure BDA0005144448040000091
Patent Text Reader

Abstract

The invention belongs to the technical field of sealants, and discloses a low-modulus high-elongation antifouling weather-resistant sealant, a preparation method and application thereof, the low-modulus high-elongation antifouling weather-resistant sealant comprises the following raw materials by weight: 100 parts of alpha, omega-dihydroxy polysiloxane, 80-200 parts of an inorganic filler, 10-30 parts of a cross-linking agent, 1-4 parts of a coupling agent, and 2-10 parts of a titanate vulcanizing agent; wherein the inorganic filler comprises active calcium carbonate and modified talcum powder; the modified talcum powder is prepared by sequentially carrying out layered stripping and modification treatment on talcum powder. The low-modulus and high-elongation antifouling sealant provided by the invention can be well suitable for joint sealing during repair of ancient buildings, and meanwhile, the product can also be extended to the field of sealing of other low-modulus antifouling buildings with the same requirements, and has high economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealants, and in particular to a low-modulus and high-elongation anti-fouling and weather-resistant sealant, a preparation method and application thereof. Background Art

[0002] Silicone materials are a type of material that is widely used in the fields of construction, aerospace, electronic and electrical insulation and sealing, rail transit, and cultural relics protection and restoration. In the field of building sealing, silicone sealants are often used for structural bonding and joint sealing of doors, windows, and curtain walls due to their good resistance to UV aging, high and low temperature resistance, and fatigue resistance, playing a role in waterproofing, moisture-proofing, heat preservation, and noise reduction.

[0003] In the restoration of ancient buildings, most of them are wooden or stone buildings. Due to the mortise and tenon structure and the fragility of wooden materials, wooden buildings need to meet a higher displacement level when sealing the joints, and at the same time, they need to withstand less stress in order to play a protective and sealing role. In the restoration of ancient buildings, it is also necessary to follow the principle of authentic restoration, and the modern materials used must not corrode or pollute the ancient buildings.

[0004] At present, sealants with low modulus and high elongation on the market often add more low-molecular plasticizers. Such plasticizers are easy to migrate and seep in the sealant system to cause pollution, while other sealants with anti-fouling properties have higher bonding strength. Excessive stress will damage the building substrate and affect the sealing effect. For example, patent No. CN113528080 B discloses a high-displacement anti-pollution silicone sealant and its preparation method. Although it has good displacement level and anti-fouling performance, the stress strength is not mentioned. At the same time, the ketoxime additives used are also corrosive to the building substrate and cannot be used for the repair of ancient buildings. Patent No. CN 114507504 B discloses a low-modulus, high-elongation single-component silicone sealant and its application. A low-modulus and high-elongation sealant was developed using a capped polymer, but a large amount of methyl silicone oil plasticizer still needs to be added to the system, which makes the sealant have certain pollution and is not suitable for the repair of ancient buildings.

[0005] Therefore, the development of a low modulus and high elongation anti-fouling sealant can be better suitable for joint sealing during the restoration of ancient buildings. At the same time, this product can also be extended to other fields that also require low modulus anti-fouling building sealing, and has high economic value. Summary of the invention

[0006] In view of the above-mentioned shortcomings that currently exist, the present invention provides a low-modulus and high-elongation anti-fouling and weather-resistant sealant, a preparation method and an application thereof. The present invention performs layered exfoliation and modification treatment on talcum powder, so that the talcum powder has good compatibility and interlayer displacement, effectively reduces the internal stress inside the sealant, and makes the sealant have lower modulus strength and higher elongation, which can effectively reduce the stress between fragile structures when sealing joints and protect buildings from damage; in the present invention, silane oligomers are selected as cross-linking agents, and the cross-linking density in the system is adjusted to further improve the elongation and reduce the modulus. At the same time, various plasticizers and small molecule cross-linking agents are not used in the present invention, and the seepage of highly active small molecule substances to form swelling, corrosion and pollution is avoided even in the initial stage of curing; the dealcoholization sealant used in the curing system releases small molecule alcohol substances that are non-corrosive to various substrates and are environmentally friendly.

[0007] In order to achieve the above object, in a first aspect, the present invention provides a low modulus and high elongation antifouling and weather-resistant sealant, comprising the following raw materials in parts by weight:

[0008] 100 parts of α,ω-dihydroxy polysiloxane, 80-200 parts of inorganic filler, 10-30 parts of crosslinking agent, 1-4 parts of coupling agent, 2-10 parts of titanate vulcanizing agent;

[0009] Wherein, the inorganic filler includes activated calcium carbonate and modified talc;

[0010] The modified talc powder is prepared by sequentially subjecting talc powder to layered flaking and modification treatment; the modified talc powder comprises the following raw materials in parts by weight:

[0011] Talc: 0-20 parts; mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate: 100 parts; modifier 1: 0.01-0.2 parts; modifier 2: 0.1-1 parts.

[0012] Wherein, the mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate has a pH value of 10.

[0013] Furthermore, the weight ratio of the activated calcium carbonate and the modified talc is (40-150) / (40-100); the modifier 1 is at least one of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-(N-cyclohexylamino)propylmethyldimethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 3-(methacryloyloxy)propylmethyldimethoxysilane, and 3-(methacryloyloxy)propylmethyldiethoxysilane; and the modifier 2 is at least one of stearic acid (salt), rosin acid (salt), coconut oil, palmitic acid (salt), gum arabic, and tannic acid.

[0014] Furthermore, the layered exfoliation step is specifically as follows: adding talc powder to a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate and stirring vigorously, and then subjecting the mixture to hydrothermal reaction, solid-liquid separation, washing the solid product, and drying to obtain intercalated talc powder.

[0015] Furthermore, the modification treatment step is specifically as follows: dissolving the intercalated talc powder in water, adding modifier 1, stirring and dispersing at 50-80° C. for 50-120 min, then adding modifier 2, stirring and dispersing at 60-80° C. for 90-180 min, and then performing solid-liquid separation, washing the solid product, and drying to obtain modified talc powder;

[0016] Furthermore, the temperature of the hydrothermal reaction is 50-80°C, and the reaction time is 50-180min.

[0017] Furthermore, the viscosity of the α,ω-dihydroxy polysiloxane at 25° C. is 5000 mPa.s to 150000 mPa.s.

[0018] Furthermore, the crosslinking agent is at least one of vinylmethoxysilane oligomer, vinylethoxysilane oligomer, and vinylmethoxyethoxysilane oligomer; the coupling agent is at least one of aminosilane polymer, epoxysilane oligomer, and acyloxysilane oligomer; and the titanate vulcanizing agent is diisopropoxytitanium bis(ethyl acetoacetate) chelate.

[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned low modulus and high elongation antifouling and weather-resistant sealant, comprising the following steps:

[0020] S1, α,ω-dihydroxy polysiloxane, nano calcium carbonate and modified talc are added into a kneader at a temperature of 80-150°C and a vacuum degree of 0.06-0.099 MPa, and dehydrated and blended for 30-300 minutes, and then cooled to obtain a base material;

[0021] S2. At room temperature, add the base material into a planetary mixer or a high-speed disperser, then add the crosslinking agent into the planetary mixer or the high-speed disperser, with a vacuum degree of 0.06 to 0.099 MPa, a rotation speed of 10 to 800 rpm, and a stirring time of 10 to 30 min. Then add the coupling agent and the phthalate vulcanizing agent into the planetary mixer or the high-speed disperser, and carry out a chemical reaction for 30 to 180 min at a vacuum degree of 0.06 to 0.099 MPa and a rotation speed of 10 to 800 rpm to obtain a low modulus and high elongation antifouling sealant.

[0022] In a third aspect, the present invention also provides the use of the above-mentioned low modulus and high elongation antifouling and weather-resistant sealant in the sealing of low modulus antifouling building joints.

[0023] Furthermore, the low modulus anti-fouling building joint sealing is the joint sealing when repairing ancient buildings.

[0024] The modification principle of the modified talcum powder of the present invention is as follows: Modifier 1 is a coupling agent with a functionality of 2, which reacts with the hydroxyl group on the surface of the talcum powder, so that the surface of the talcum powder has certain reaction sites, which can improve the bonding strength between the powder and the polymer and improve the elongation, but at the same time, the cross-linking point is a functionality of 2, which can well control its cross-linking density, reduce the cohesion and control the modulus growth. Modifier 2 is used as a coating agent to make the surface of the modified powder hydrophilic / oleaginous, which can improve the compatibility of the powder with the polymer (first using modifier 2 to coat and then using modifier 1 for modification will seriously affect the modification effect of modifier 1).

[0025] Beneficial effects of the present invention:

[0026] (1) After the talc powder is subjected to layered peeling and modification, the (modified talc powder) can reduce the internal stress to soften the rubber strip and reduce the modulus. When subjected to external pressure, the sliding between the modified talc powder layers can absorb energy well and effectively improve the elongation. At the same time, the modification also improves the compatibility and mechanical properties of the powder and the polymer, making the system more stable;

[0027] (2) The present invention uses silane oligomers as crosslinking agents, which can adjust the crosslinking density in the system. The powder modification further improves the elongation of the sealant and reduces the modulus.

[0028] (3) The system of the present invention does not use any plasticizers, which can effectively prevent pollution caused by the migration of plasticizers. At the same time, the oligomeric cross-linking agent used can prevent the auxiliary agent from migrating quickly in the early stage of curing, thereby reducing the foaming and corrosion caused by poor compatibility with the substrate surface, especially the porous wooden substrate;

[0029] (4) The present invention adopts a dealcoholization system, and the small molecule alcohol substances released during the curing process are relatively environmentally friendly, low-toxic and non-corrosive. DETAILED DESCRIPTION

[0030] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0031] Example 1

[0032] A method for preparing a low modulus and high elongation antifouling and weather-resistant sealant:

[0033] (1) Preparation method of modified talcum powder

[0034] a. Take 20 parts of talc and add them to 100 parts of a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate (pH = 10) and stir vigorously. After hydrothermal reaction at 80°C for 2h, separate the solid and liquid and collect the solid product. After washing and drying, the intercalated talc is obtained.

[0035] b. Take 20 parts of the above intercalated talc, add 50 parts of water and stir and disperse, add 0.1 parts of 3-aminopropylmethyldimethoxysilane, continue stirring and dispersing at 60°C for 1h, add 0.5 parts of sodium stearate, continue stirring and dispersing at 60°C for 2h, perform solid-liquid separation and collect the solid product, wash and dry to obtain modified talc.

[0036] (2) Preparation method of low modulus and high elongation antifouling and weather-resistant sealant

[0037] A. Take 80 parts of α,ω-dihydroxypolysiloxane (50000mPa.s) and 100 parts of nano calcium carbonate / modified talc (mass ratio 3:2) and add them into a kneader, the temperature is 120°C, the vacuum degree is -0.099MPa, dehydrate and blend for 120 minutes, and obtain the base material after cooling.

[0038] B. At room temperature, add the above base materials into a planetary mixer or a high-speed disperser, then add 20 parts of vinyl methoxy silane oligomer into the planetary mixer or a high-speed disperser, vacuum degree -0.06MPa, rotation speed 400rpm, stirring time 10 minutes, then add 3 parts of coupling agent (the mass ratio of aminosilane polymer to epoxysilane oligomer is 2:1) and 5 parts of diisopropoxy titanium di(ethyl acetoacetate) chelate into the planetary mixer or a high-speed disperser at a vacuum degree of -0.099MPa and a rotation speed of 400rpm for 45 minutes to make a low modulus and high elongation antifouling sealant.

[0039] Example 2

[0040] A method for preparing a low modulus and high elongation antifouling and weather-resistant sealant:

[0041] (1) Preparation method of modified talcum powder

[0042] a. Take 20 parts of talc and add them to 100 parts of a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate (pH = 10) and stir vigorously. After hydrothermal reaction at 80°C for 2h, separate the solid and liquid and collect the solid product. After washing and drying, the intercalated talc is obtained.

[0043] b. Take 20 parts of the above talcum powder, add 50 parts of water and stir and disperse, then add 0.1 parts of 3-(N-cyclohexylamino)propylmethyldimethoxysilane, continue stirring and dispersing at 60°C for 1h, add 0.5 parts of sodium palmitate, continue stirring and dispersing at 60°C for 2h, perform solid-liquid separation and collect the solid product, wash and dry to obtain modified talcum powder.

[0044] (2) Preparation method of low modulus and high elongation antifouling and weather-resistant sealant

[0045] A. Take 80 parts of α, ω-dihydroxy polysiloxane (12000-50000 mPa.s) and 100 parts of nano calcium carbonate / modified talc (mass ratio 3:2) and add them into a kneader, the temperature is 120°C, the vacuum degree is -0.099 MPa, dehydrate and blend for 120 minutes, and obtain the base material after cooling.

[0046] B. At room temperature, add the above base materials into a planetary mixer or a high-speed disperser, then add 20 parts of vinylethoxysilane oligomer into the planetary mixer or high-speed disperser, vacuum degree 0.06MPa, rotation speed 400rpm, stirring time 10 minutes, then add 3 parts of coupling agent (the mass ratio of aminosilane polymer to epoxysilane oligomer is 2:1) and 5 parts of diisopropoxytitanium di(ethyl acetoacetate) chelate into the planetary mixer or high-speed disperser at a vacuum degree of -0.099MPa and a rotation speed of 400rpm for 45 minutes to make a low modulus and high elongation antifouling sealant.

[0047] Example 3

[0048] A method for preparing a low modulus and high elongation antifouling and weather-resistant sealant:

[0049] (1) Preparation method of modified talcum powder

[0050] a. Take 10 parts of talc and add them to 100 parts of a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate (pH = 10) and stir vigorously. After hydrothermal reaction at 80°C for 2h, separate the solid and liquid and collect the solid product. After washing and drying, the intercalated talc is obtained.

[0051] b. Take 20 parts of the above talcum powder, add 50 parts of water and stir and disperse, add 0.2 parts of 3-glycidyloxypropylmethyldimethoxysilane, continue stirring and dispersing at 60°C for 1h, add 0.5 parts of rosin acid, continue stirring and dispersing at 60°C for 2h, perform solid-liquid separation and collect the solid product, wash and dry to obtain modified talcum powder.

[0052] (2) Preparation method of low modulus and high elongation antifouling and weather-resistant sealant

[0053] A. Take 100 parts of α,ω-dihydroxypolysiloxane (12000-50000 mPa.s) and 100 parts of nano calcium carbonate / modified talc (mass ratio 3:2) and add them into a kneader, the temperature is 120°C, the vacuum degree is -0.099 MPa, dehydrate and blend for 120 minutes, and obtain the base material after cooling.

[0054] B. At room temperature, add the above base material into a planetary mixer or a high-speed disperser, then add 20 parts of vinyl methoxyethoxy silane oligomer into the planetary mixer or high-speed disperser, vacuum degree -0.06MPa, rotation speed 400rpm, stirring time 10 minutes, then add 3 parts of coupling agent (the mass ratio of aminosilane polymer to acyloxysilane oligomer is 2:1) and 5 parts of diisopropoxy titanium di(ethyl acetoacetate) chelate into the planetary mixer or high-speed disperser at a vacuum degree of -0.099MPa and a rotation speed of 400rpm for 45 minutes to make a low modulus and high elongation antifouling sealant.

[0055] Example 4

[0056] A method for preparing a low modulus and high elongation antifouling and weather-resistant sealant:

[0057] (1) Preparation method of modified talcum powder

[0058] a. Take 20 parts of talc and add them to 100 parts of a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate (pH = 10) and stir vigorously. After hydrothermal reaction at 80°C for 2h, separate the solid and liquid and collect the solid product. After washing and drying, the intercalated talc is obtained.

[0059] b. Take 20 parts of the above talc, add 50 parts of water and stir and disperse, then add 0.1 parts of 3-glycidyloxypropylmethyldiethoxysilane and 3-(methacryloyloxy)propylmethyldiethoxysilane, continue stirring and dispersing at 60°C for 1h, add 0.5 parts of stearic acid, continue stirring and dispersing at 60°C for 2h, perform solid-liquid separation and collect the solid product, wash and dry to obtain modified talc.

[0060] (2) Preparation method of low modulus and high elongation antifouling and weather-resistant sealant

[0061] A. Take 80 parts of α, ω-dihydroxy polysiloxane (12000-50000 mPa.s) and 100 parts of nano calcium carbonate / modified talc (mass ratio 1:1) and add them into a kneader, the temperature is 120°C, the vacuum degree is -0.099 MPa, dehydrate and blend for 120 minutes, and obtain the base material after cooling.

[0062] B. At room temperature, add the above base material into a planetary mixer or a high-speed disperser, then add 20 parts of vinylethoxysilane oligomer into the planetary mixer or high-speed disperser, vacuum degree -0.06MPa, rotation speed 400rpm, stirring time 10 minutes, then add 3 parts of coupling agent (the mass ratio of aminosilane polymer to acyloxysilane oligomer is 1:1) and 5 parts of diisopropoxytitanium di(ethyl acetoacetate) chelate into the planetary mixer or high-speed disperser at a vacuum degree of -0.099MPa and a rotation speed of 400rpm for 45 minutes to make a low modulus and high elongation antifouling sealant.

[0063] Example 5

[0064] A method for preparing a low modulus and high elongation antifouling and weather-resistant sealant:

[0065] (1) Preparation method of modified talcum powder

[0066] a. Take 10 parts of talc and add them to 100 parts of a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate (pH = 10) and stir vigorously. After hydrothermal reaction at 80°C for 2h, separate the solid and liquid and collect the solid product. After washing and drying, the intercalated talc is obtained.

[0067] b. Take 20 parts of the above talcum powder, add 50 parts of water and stir and disperse, add 0.2 parts of 3-(methacryloyloxy)propylmethyldimethoxysilane, continue to stir and disperse at 60°C for 1h, add 0.5 parts of tannic acid, continue to stir and disperse at 60°C for 2h, perform solid-liquid separation and collect the solid product, wash and dry to obtain modified talcum powder

[0068] (2) Preparation method of low modulus and high elongation antifouling and weather-resistant sealant

[0069] A. Take 100 parts of α,ω-dihydroxypolysiloxane (50000mPa.s) and 100 parts of nano calcium carbonate / modified talc (mass ratio 1:1) and add them into a kneader, the temperature is 120°C, the vacuum degree is -0.099MPa, dehydrate and blend for 120 minutes, and obtain the base material after cooling.

[0070] B. At room temperature, add the above base material into a planetary mixer or a high-speed disperser, then add 20 parts of vinylethoxysilane oligomer into the planetary mixer or high-speed disperser, vacuum degree -0.06MPa, rotation speed 400rpm, stirring time 10 minutes, then add 3 parts of coupling agent (the mass ratio of aminosilane polymer to acyloxysilane oligomer is 1:1) and 5 parts of diisopropoxytitanium di(ethyl acetoacetate) chelate into the planetary mixer or high-speed disperser at a vacuum degree of -0.099MPa and a rotation speed of 400rpm for 45 minutes to make a low modulus and high elongation antifouling sealant.

[0071] Comparative Example 1

[0072] The difference between this comparative example and Example 1 is that modified talc is not used. Other aspects are the same as Example 1.

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 1 is that 20 parts of dimethyl silicone oil are additionally added to the silicone sealant, 20 parts of methyltrimethoxysilane are used, and 3 parts of coupling agent (γ-aminopropylethoxysilane: epoxypropyltriethoxysilane=2:1) ​​are used as coupling agent. Others are the same as Example 1.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 1 is that the modified talc powder is only subjected to layering and exfoliation without modification. The other aspects are the same as Example 1.

[0077] Comparative Example 4

[0078] The difference between this comparative example and Example 1 is that the modified talc powder is not subjected to stratification and flaking, but only subjected to modification treatment. The other aspects are the same as those of Example 1.

[0079] Performance testing and result analysis:

[0080] Test method for mechanical properties of silicone sealant: The test is carried out in accordance with the regulations and standards of GB / T14683-2017 "Silicone and modified silicone building sealants", of which the tensile adhesion is tested in accordance with GB / T13477.8-2017 "Test methods for building sealing materials", and the contamination test is carried out in accordance with the standard method in Appendix A of GB / T 23261-2009 "Building sealants for stone".

[0081] The substrate used for the compatibility test between the sealant and the substrate surface at the initial stage of curing is a natural granite with a smooth surface and no treatment. The test method is to apply the sealant on the granite surface to trim a small thin piece with a length, width and height of 100*50*3mm. Without demolding, it is immediately placed in a 70℃ oven for accelerated curing for 24 hours. Finally, observe whether small bubbles are formed on the surface of the film on the granite. The test results are shown in Table 1 below:

[0082] Table 1:

[0083]

[0084] Note: S1, S2, S3, S4, S5 in Table 1 refer to Example 1, Example 2, Example 3, Example 4, Example 5 respectively; D1, D2, D3, D4 refer to Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 respectively.

[0085] It can be seen from Table 1 above that the talc powder in Examples 1 to 5 can effectively reduce the cohesive force after exfoliation and modification, so that the sealant has a lower modulus and a higher elongation. The modulus reduction effect of the talc powder is different due to the influence of different treatment agents. At the same time, the solution concentration used for exfoliation and the glue / powder ratio used in the preparation of the sealant will also have a slight effect on the performance. However, as a whole, the requirements of low modulus, high elongation and anti-fouling can be well achieved. In Comparative Example 1, the modulus is significantly improved without using talcum powder. This is because the reinforcing ability of pure nano calcium carbonate is good, and the cohesive force is too high, which causes the rubber strip to harden; although modified talcum powder is used in Comparative Example 2, the selected small molecule additive has a higher molar mass than the oligomeric cross-linking agent at the same weight, resulting in a higher cross-linking density. The modulus is 0.45MPa when silicone oil is added, which belongs to the upper limit of the low modulus. At the same time, the addition of silicone oil also causes pollution. After using the low molecular cross-linking agent, the compatibility with the stone becomes worse, and there is slight foaming; Comparative Examples 3 and Comparative Examples 4 are respectively modified and intercalated, and Comparative Example 3 without modification This makes the compatibility of the powder with polysiloxane worse, and the reinforcement effect, thixotropy and elastic recovery rate all worse. Although the modulus of comparative example 1 is reduced, it still belongs to high modulus, and the displacement level also fails to meet the requirement of level 50; while comparative example 4 does not undergo talcum powder exfoliation and layering treatment. Although its strength is low, its elastic recovery rate is poor, which easily leads to the sealant being unable to rebound and lose its sealing performance. This is mainly caused by the original talcum powder crystals being too thick and the interlayer sliding after being stressed being too large, resulting in the crystal form being destroyed and unable to recover, thereby affecting the overall elasticity of the sealant. It is necessary to reduce the crystal thickness and control the deformation through exfoliation and layering treatment.

[0086] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A low modulus and high elongation antifouling and weather-resistant sealant, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of α,ω-dihydroxy polysiloxane, 80-200 parts of inorganic filler, 10-30 parts of crosslinking agent, 1-4 parts of coupling agent, 2-10 parts of titanate vulcanizing agent; Wherein, the inorganic filler includes activated calcium carbonate and modified talc; The modified talc powder is prepared by sequentially subjecting talc powder to layered flaking and modification treatment; the modified talc powder comprises the following raw materials in parts by weight: Talc: 0-20 parts; mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate: 100 parts; modifier 1: 0.01-0.2 parts; modifier 2: 0.1-1 parts.

2. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 1, characterized in that: The weight ratio of the activated calcium carbonate and the modified talc is (40-150) / (40-100); the modifier 1 is at least one of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-(N-cyclohexylamino)propylmethyldimethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 3-(methacryloyloxy)propylmethyldimethoxysilane, and 3-(methacryloyloxy)propylmethyldiethoxysilane; the modifier 2 is at least one of stearic acid (salt), rosin acid (salt), coconut oil, palmitic acid (salt), gum arabic, and tannic acid.

3. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 1, characterized in that: The step of layered exfoliation is specifically as follows: adding talc powder into a mixed solution of sodium hydroxide and sodium dodecylbenzene sulfonate and stirring vigorously, and then subjecting the mixture to hydrothermal reaction, solid-liquid separation, washing the solid product, and drying to obtain intercalated talc powder.

4. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 3, characterized in that: The modification treatment steps are specifically as follows: dissolving the intercalated talc powder into water, adding modifier 1, stirring and dispersing at 50-80° C. for 50-120 min, then adding modifier 2, stirring and dispersing at 60-80° C. for 90-180 min, and then performing solid-liquid separation, washing the solid product, and drying to obtain the modified talc powder.

5. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 50-80° C., and the reaction time is 50-180 min.

6. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polysiloxane at 25° C. is 5000 mPa.s to 150000 mPa.s.

7. The low modulus and high elongation antifouling and weather-resistant sealant according to claim 1, characterized in that: The crosslinking agent is at least one of vinylmethoxysilane oligomer, vinylethoxysilane oligomer and vinylmethoxyethoxysilane oligomer; the coupling agent is at least one of aminosilane polymer, epoxysilane oligomer and acyloxysilane oligomer; the titanate vulcanizing agent is diisopropoxytitanium bis(ethyl acetoacetate) chelate.

8. The method for preparing the low modulus and high elongation antifouling and weather-resistant sealant according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, α,ω-dihydroxy polysiloxane, nano calcium carbonate and modified talc are added into a kneader at a temperature of 80-150°C and a vacuum degree of 0.06-0.099 MPa, and dehydrated and blended for 30-300 minutes, and then cooled to obtain a base material; S2. At room temperature, add the base material into a planetary mixer or a high-speed disperser, then add the crosslinking agent into the planetary mixer or the high-speed disperser, with a vacuum degree of 0.06 to 0.099 MPa, a rotation speed of 10 to 800 rpm, and a stirring time of 10 to 30 min. Then add the coupling agent and the phthalate vulcanizing agent into the planetary mixer or the high-speed disperser, and carry out a chemical reaction for 30 to 180 min at a vacuum degree of 0.06 to 0.099 MPa and a rotation speed of 10 to 800 rpm to obtain a low modulus and high elongation antifouling sealant.

9. Use of the low modulus and high elongation antifouling and weather-resistant sealant as claimed in any one of claims 1 to 7 or the low modulus and high elongation antifouling and weather-resistant sealant prepared by the preparation method of claim 8 in sealing low modulus antifouling building joints.

10. The use according to claim 9, characterized in that: The low modulus antifouling building joint sealing is used for joint sealing during the restoration of ancient buildings.

Citation Information

Patent Citations

  • A high-displacement anti-fouling silicone sealant and its preparation method

    CN113528080B

  • A low-modulus, high-elongation one-component silicone sealant and its application

    CN114507504B

  • Halogen-free flame-retardant heat-conduction organosilicon electronic pouring sealant and preparation technology thereof

    CN102618208A

  • Preparation method and application of high impact-resistant modified talcum powder

    CN106397967A

  • Building sealant and preparation method thereof

    CN106634801A